Supporting teacher professionalism through tailored professional learning (UCL Press, 2019)
The issue of continuing professional learning for educators in the early childhood education and care sector is in the spotlight in Australia due to the government's reform agenda, which seeks to professionalize the workforce. In an effort to ensure quality programmes are on offer for all children, educators are expected to upskill. The assumption is that quality learning opportunities for children are aligned with a more skilled and capable workforce. This is problematic due to the diversity of the early childhood education and care workforce and its ability to convert professionalization opportunities into achievements. The focus of this article is a study that problematized the alignment of professional attributes valued in the policy space and in the field of practice to understand educator agency, a key element of professional capability. Once this alignment is known, professional learning experiences can be tailored to better support the professionalization of these educators.